Digital Mading Training In Supporting Reading and Writing Literacy At SMPN 3 Rambah - Dahlia; Dona; Rena Lestari; Ajeng Febiola; Septi Dwiyanti (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2023)
Media Canva is a web-based online graphic design and visual communication platform that allows users to easily create various types of visual materials, posters, presentations, social media, and instant animations or templates. This Canva-based digital media training aims to train teachers and students in creating attractive and well-managed digital media to support students' reading and writing literacy in schools. SMPN 3 Rambah has conventional madding. These conventional media have weaknesses that cause problems for the school, such as, the media are less attractive, the condition of the media is inadequate and there is no system for managing the media. It is hoped that the results of this training will produce digital media as an information medium as well as a place for students' creativity and as a forum for improving reading and writing literacy skills for teachers and students that are easily accessible anywhere and anytime. The result of this training is an understanding of designing digital media, the existence of digital media websites and managing digital media